Use of Omental Flap in the Management of Postoperative Mediastinitis - ElmustafaHassan, SalahEldin Mohamed; H.Morsy, Sameh (Gezira Journal of Health Sciences, 2015)
Introduction: Post sternotomy infections are a dreadful havoc of modern cardiac surgery.General complications of wound healing include hypertrophic and keloid scars, sterna wires sinus and failure of healing in the form of mediastinal dehiscence and infections. Methodology: This study was conducted in National Heart Institute, Imbaba, and Cairo Egypt in the period between January 2006 to January 2009. During that period, we faced repeated problems of sternal wound infection after open heart surgery, some of them were serious and the majority were resolving and self limiting. We used Omental flap in 7 patients with life-threatening Mediastinitis, 4 of them were females and three were males of age range 54-68 years. All of the patients were diabetics type II and all females had body mass index more than 35. One of the male patients was of body mass index 33 and the other was 30.The primary operation was CABG in all patients and we used LIMA in all of them. We didn't use bilateral mammary in any patient. Results: In this study two patients died, one male patient died 48 hours after the flap procedure and the other was a female patient who died after two weeks from the procedure. The rest of the patients were in good health and were discharged and being followed up now for a period of 18 months. Conclusions: Omental flap is a useful relatively easy procedure that can be invaluable in the treatment of advanced mediastinitis following open heart procedures utilizing median sternotomy.